THE IMPACT OF COVID-19 PANDEMIC ON EDUCATION AND JUDICIAL PRACTICE IN INDONESIA - Zainal Abidin; Tobibatussa'adah Tobibatussa'adah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2020)
The corona virus has made fundamental changes to educational and legal practices in Indonesia. The large number of Covid-19 cases that have occurred in Indonesia makes holding state policies must be active to tackle the spread of this deadly virus, one of which is changing the pattern and model of education including trial administration using online media depending on the zone categorization set by the government. This paper finds out what happened during the Indonesian pandemic. First, in education, the emergence of covid-19 has made significant changes in the learning process by utilizing online learning media, and students are starting to be sent home, including in the context of higher education. Second, in the field of justice , trial administration in a number of courts is still carried out with due observance of health protocols, some trials are also conducted using an online trial model using various media, so that the law enforcement process continues. This paper also explains that the Covid-19 pandemic has become the center of serious attention of the government, including in providing education and implementing judicial processes in the world of law in Indonesia. Or in other words that even in the midst of a pandemic, activities must continue in various aspects, especially during the new normal era.